Novel Microstructural Features on Heat and Mass Transfer in Peristaltic Flow Through a Curved Channel - Ahmed, Raheel; Ali, Nasir; Khan, Sami Ullah; Rashad, A. M.; Nabwey, Hossam A.; Tlili, Iskander (Frontiers in Physics, 2020)
Recently, significant interest has been developed by researchers towards the peristaltic transport of fluid as this phenomenon involves variety of applications in bio-mechanics, bio-engineering and biomedical industry. In present contribution, we investigate the effect of heat and mass transfer on magnetically influenced micropolar flow induced by peristaltic waves. The equations describing the flow and heat/ mass transfer are developed using curvilinear coordinates. A reduction of these equations is made based on lubrication approximation. Implicit finite difference scheme is employed to solve the set of reduced linear ordinary differential equations. The effects of coupling number, micropolar parameter, Hartmann number, Brinkmann number, rate of chemical reaction and curvature parameter on longitudinal velocity, pressure rise, temperature and mass concentration are analyzed in detail. The flow patterns in the channel illustrating the effects of several involved parameter are also displayed.